THE MODERATING OF POLLITICAL CONNECTION ON FACTORS AFFECTING FRAUDULENT FINANCIAL STATEMENT FROM THE PENTAGON FRAUD MODEL PERSPECTIVE - Irawan, Helmiansyah; Aryati, Titik (Archives of Business Research, 2021)
ABSTRACT The Purpose of this research is to analyze the effect of the factors that effect of fraud in financial statements that occur in companies. And also analyzes the impact of political connections as a moderating variable that strengthens or weakens the factors that influences fraud in the financial statements.The author collects empirical study data from manufacture industry companies, using secondary data taken from annual reporting of companies listed in the Indonesia Stock Exchange and analyzes them using the SPSS program. A total of 60 units of data analysis that meet the criteria and can be used as sample in the research. This research reveals that effective monitoring and change of director has a positive and significant effect on financial statement of fraudulent. A set of financial targets, changes of auditors, and the frequencies of CEO pictures have not effect on fraudulent of financial statement. Whatever, the impact on political connection as oderating variable only strengthens the influence between effective monitoring and change of BOD on fraudulent financial statement from before being moderated by the political connection. This study only takes data of secondary from the annual reporting of companies and financial reports of firm from BEI, especially the manufacturing industry which only covers three sectors. Meanwhile, the Indonesia Stock Exchange consists of nine existing industrial sectors. Originality/value for this research is Political Connection as a moderator between financial stability, in effectively monitoring, change of auditor, change of director and frequencies of number commissioner’s pictures on financial statement of fraudulent in the context of manufacture companies listed in BEI is still little researched. So this research will not only fill in the current gaps in the literature but also spark new academic debates, but this study will also contribute to the practice of fraudulent financial. Keywords: financial stability, ineffectively monitoring, changes of auditor, changes of director, financial statement of fraudulent